Microbiome dysbiosis in SARS-CoV-2 infection: implication for pathophysiology and management strategies of COVID-19 - Smail, Shukur Wasman; Albarzinji, Niaz; Salih, Rebaz Hamza; Taha, Kalthum Othman; Hirmiz, Sarah Mousa; Ismael, Hero M.; Noori, Marwa Fateh; Azeez, Sarkar Sardar; Janson, Christer (Frontiers in Cellular and Infection Microbiology, 2025)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of coronavirus disease 2019 (COVID-19), in late 2019 initiated a global health crisis marked by widespread infection, significant mortality, and long-term health implications. While SARS-CoV-2 primarily targets the respiratory system, recent findings indicate that it also significantly disrupts the human microbiome, particularly the gut microbiota, contributing to disease severity, systemic inflammation, immune dysregulation, and increased susceptibility to secondary infections and chronic conditions. Dysbiosis, or microbial imbalance, exacerbates the clinical outcomes of COVID-19 and has been linked to long-COVID, a condition affecting a significant proportion of survivors and manifesting with over 200 symptoms across multiple organ systems. Despite the growing recognition of microbiome alterations in COVID-19, the precise mechanisms by which SARS-CoV-2 interacts with the microbiome and influences disease progression remain poorly understood. This narrative review investigates the impact of SARS-CoV-2 on host-microbiota dynamics and evaluates its implications in disease severity and for developing personalized therapeutic strategies for COVID-19. Furthermore, it highlights the dual role of the microbiome in modulating disease progression, and as a promising target for advancing diagnostic, prognostic, and therapeutic approaches in managing COVID-19.